Bridging Nature and Technology: The Impact of Environment-Based Augmented Reality Digital Books on Elementary Students’ Science Interest and Achievement - Susilawati, Luh Putu; Dantes, Nyoman; Ardana, I Made (Jurnal Paedagogy, 2026)
This study aims to develop a digital book design equipped with environment-based Augmented Reality (AR) features and to examine its validity, practicality, and effectiveness in improving students’ interest and achievement in science learning. This study employed the ADDIE model, consisting of five stages: Analyze, Design, Development, Implementation, and Evaluation. The research was conducted with fifth-grade students at SD No. 3 Kedonganan, Bali Province. The effectiveness test involved 54 students from two classes, consisting of 27 students in the experimental class and 27 students in the control class. The practicality test involved five teachers and 25 fifth-grade students selected for the product trial. Data were collected through validated questionnaires and multiple-choice tests. The validity of the digital book was assessed using a modified Learning Object Review Instrument (LORI) and BSNP assessment instruments. The developed digital book integrates 3D visualization and AR features. The validity test results showed that the digital book achieved an average score of 0.92, indicating a very valid category. The practicality results showed that teacher responses reached an average score of 95.16%, while student responses reached 92.53%, both categorized as very practical. The hypothesis testing results using one-way MANOVA showed a significance value of p < 0.001, indicating a statistically significant effect of implementing the environment-based AR digital book on students’ interest and achievement in science learning. These findings indicate that the developed digital book with environment-based AR features is a valid, practical, and effective learning medium for enhancing science learning outcomes and interest among fifth-grade elementary school students.